Reading With EDSAW Acronym at Tertiary Level - Revathi Gopal; Magdelena Long Mering (English Education Journal, 2022)
This study aims to explore the use of the EDSAW acronym, a reading strategy in locating contextual clues systematically among tertiary-level students. It takes a quantitative research design to answer the research question, ‘How effective is the use of the EDSAW acronym in comprehending a reading text?’ The sample was selected based on a purposive sampling technique that comprised 10 students from a public university who scored band 4 in the Malaysian University English Test (MUET). The data collection technique involves a pre-test and a post-test. A reading text was given during the pre-test where students were tasked to locate contextual clues without using the EDSAW acronym. Then, the same participants were taught to use the acronym in finding contextual clues in a reading text. The mean scores of the pre-test and post-test were compared. The findings revealed that there was a significant increase of 2.3 points in the mean score of the post-test. This study highlights the need for teachers and students to use the reading strategy EDSAW acronym during the teaching and learning of reading in ESL classrooms and fills a void in the area of reading comprehension by enabling students to read more independently.